2017
DOI: 10.3758/s13421-017-0726-z
|View full text |Cite
|
Sign up to set email alerts
|

Repetition blindness in priming in perceptual identification: Competitive effects of a word intervening between prime and target

Abstract: University students named a 72-ms masked target word that was preceded by two 120-ms consecutively presented words, a prime word followed by a distractor. In Experiment 1, all words were in lowercase letters, whereas in Experiment 2, the target word was changed to uppercase letters. In both experiments there was an accuracy and latency cost (repetition blindness: RB) when the prime was the same word as the target, with the cost much less severe in Experiment 2 than in Experiment 1. A low-frequency distractor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 32 publications
(70 reference statements)
7
14
0
Order By: Relevance
“…Finally, the repetition cost remained significant for both high- and low-frequency targets when participants were alerted to the presence of repeats. The observation of repetition costs is consistent with the studies of Burt and Jolley (2017), and inconsistent with both the repetition benefits in single-word-trial studies of perceptual identification (Feustel et al, 1983), and the ubiquitous findings of repetition priming benefits when the target remains in view for naming or lexical decision (Burt et al, 2014).…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Finally, the repetition cost remained significant for both high- and low-frequency targets when participants were alerted to the presence of repeats. The observation of repetition costs is consistent with the studies of Burt and Jolley (2017), and inconsistent with both the repetition benefits in single-word-trial studies of perceptual identification (Feustel et al, 1983), and the ubiquitous findings of repetition priming benefits when the target remains in view for naming or lexical decision (Burt et al, 2014).…”
Section: Discussionmentioning
confidence: 41%
“…According to Morris et al (2009), a high-frequency word has a sharpened representation and can be more vulnerable to competition from adjacent items. Some evidence in support of this prediction was reported by Burt and Jolley (2017), but only for unrelated prime trials. On the model, when word identifiability is lower (input noise is high), the magnitude of RB decreases.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The results of Experiment 1 also showed identical patterns of performance in the full-report condition, in which participants reported all items in the RSVP stream, and the partialreport condition, in which participants only reported the last item in the stream. A difference between these conditions was used by Kanwisher as one of the main arguments for the token-individuation account, although subsequent studies have failed to replicate that difference (Burt & Jolley, 2017;Kanwisher & Potter, 1990;Leggett et al, 2019;Luo & Caramazza, 1995). Therefore, the strong evidence we found for equivalent patterns of performance between partial-report and full-report conditions is also more in line with an explanation in terms of a failure at the level of type identification than a failure to individuate the items, since the partial-report condition does not enforce token individuation.…”
Section: Discussionmentioning
confidence: 99%
“…However, Kanwisher's original grounds for rejecting the type refractoriness hypothesis are challenged by a number of failures to replicate the finding that an unattended C1 yields priming rather than RB. These experiments have shown that RB can be obtained even when C1 is not reported (Burt & Jolley, 2017;Kanwisher & Potter, 1990;Leggett et al, 2019;Luo & Caramazza, 1995), leaving open the possibility that RB can be caused by difficulties in establishing a robust type representation. This was examined in the current study.…”
mentioning
confidence: 99%